(untitled) (Castilla. Estudios de Literatura, 2012)
The classical myth is one of the most important artistic expressions in our cultural and literary tradition. However, the fact that the teaching of this subject is associated to a specific area of courses considered optional implies that many of the secondary school (ESO) students end their studies with scarce knowledge about the classical myth. In this article, my intention is to show the necessity of including this particular aspect in the secondary school literature curricula and I illustrate it with Ovid’s Metamorphoses.